Halophytes for the sustainable remediation of heavy metal-contaminated sites: Recent developments and future perspectives. (February 2023) - Singh, Vipin Kumar; Singh, Rishikesh; Rajput, Vishnu D.; Singh, Vivek Kumar
Abstract: Increasing land degradation by high level of metal wastes is of prime concern for the global research communities. In this respect, halophytes having specific features like salt glands, exclusion of excess ions, heavy metals (HMs) compartmentalization, large pool of antioxidants, and associations with metal-tolerant microbes are of great promise in the sustainable clean-up of contaminated sites. However, sustainable clean-up of HMs by a particular halophyte plant species is governed considerably by physico-chemical characteristics of soil and associated microbial communities. The present review has shed light on the superiority of halophytes over non-halophytes, mechanisms of metal-remediation, recent developments and future perspectives pertaining to the utilization of halophytes in management of HM-contaminated sites with the aid of bibliometric analysis. The results revealed that the research field is receiving considerable attention in the last 5–10 years by publishing ∼50–90% documents with an annual growth rate of 15.41% and citations per document of 29.72. Asian (viz., China, India, and Pakistan) and European (viz., Spain, Portugal, Belgium, Argentina) countries have been emerged as the major regions conducting and publishing extensive research on this topic. The investigations conducted both under in vitro and field conditions have reflected the inherent potential of halophyte as sustainable research tool for successfully restoring the HM-contaminated sites. The findings revealed that the microbial association with halophytes under different challenging conditions is a win-win approach for metal remediation. Therefore, exploration of new halophyte species and associated microorganisms (endophytic and rhizospheric) from different geographical locations, and identification of genes conferring tolerance and phytoremediation of metal contaminants would further advance the intervention of halophytes for sustainable ecological restoration. Graphical abstract: Image 1 Highlights: Bibliometric analysis on halophyte assisted HMs remediation was carried out. Potential implications of halophyte in restoration of HMs contaminated sites is explored. Contribution of halophyte-assisted microbes in improved remediation is highlighted. Influence of environmental factors on halophyte aided remediation has been identified. Future research perspectives on halophyte-mediated phytoremediation is highlighted.